Models for Machining Accuracy in Multi-Tool Adjustment - Yusubov, Nizami; Abbasova, Heyran (Universiti Malaysia Pahang Al-Sultan Abdullah Press (UMPSA Press), 2020)
The article discusses the technology capabilities of multi-purpose CNC machines, and possible options for implementing parallel multi-tool processing. It was revealed that the technological capabilities of these machines are used at best by 50% in factories. This is due to the lack of recommendations for the design and use of such adjustments for these machines. To this end, generalised lattice matrix models of the accuracy of multi-tool machining have been developed in order to fulfill the requirements of algorithmic uniformity models and their structural transparency. The use of lattice matrices greatly simplifies the error in model of multi-tool machining and makes it extremely visual. Also, full-factorial distortion models and scattering fields of the dimensions of multi-tool machining performed on modern multi-purpose CNC lathe machines have been developed to take into account the angular displacements of the workpiece when machining parts with prevailing overall dimensions. They take into account the flexibility of the technological system for all six degrees of freedom to identify the influence degree of complex of technological factors on the machining accuracy (structure of multi-tool adjustment, deformation properties of subsystems of a technological system, cutting conditions). A methodology has been developed for determining the complex characteristics of compliance of a technological system. On the basis of the developed accuracy models in spatial adjustments, it is possible to develop recommendations for the design of adjustments for modern multi-purpose machines in CNC turning group (creation of CAD of multi-tool machining). Thus, it is possible to achieve a number of ways to control multi- tool machining, including improving the structure of multi-tool adjustment, calculating the limiting cutting conditions.
Keywords: Models for machining accuracy; Multi-tool machining; Multi-purpose CNC machines; Lattice matrix models of accuracy; Full-factor models of accuracy